Electrochromic polymer and its preparation method and application

By introducing a single alkoxy group on the quinoxalinyl group of the electrochromic polymer, the problems of stability and solubility of the electrochromic material are solved, and efficient electrochromic effect and excellent performance are achieved.

CN115785402BActive Publication Date: 2025-02-07SUZHOU OPAK DISPLAY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211516738.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-29
Publication Date
2025-02-07
Estimated Expiration
2042-11-29

AI Technical Summary

Technical Problem

There are stability problems in existing electrochromic materials in practical applications, especially the composition of the electrochromic layer affects its stability, and it is difficult to increase its solubility for entry of doped particles without increasing steric resistance.

Method used

By designing the structure of the electrochromic polymer, introducing quinoxaline groups and introducing a single alkoxy group thereto, improving its solubility and avoiding large steric hindrance, it is suitable for the preparation of electrochromic devices. chromogenic layer.

Benefits of technology

It achieves high solubility and excellent performance of electrochromic polymers, with high optical contrast, good cycle stability, short fading and coloring time, and high coloring efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115785402B_ABST
    Figure CN115785402B_ABST
Patent Text Reader

Abstract

The present invention provides an electrochromic polymer and a preparation method and application thereof. The electrochromic polymer has a structure as shown in Formula I. In the present invention, by designing the structure of the electrochromic polymer, the prepared electrochromic polymer has a large solubility and does not generate a large steric hindrance, thereby not hindering the entry of doped particles, and is suitable for being used as an electrochromic material to prepare an electrochromic device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochromic materials, and in particular relates to an electrochromic polymer and a preparation method and application thereof. Background Art

[0002] Electrochromism refers to the phenomenon that the optical properties (transmittance or reflectance, etc.) of a material undergo stable and reversible changes in the visible light range under the drive of an applied voltage. In terms of appearance, electrochromic (EC) materials usually show reversible changes in color and transparency. Currently, there are many electrochromic (EC) devices that use electrochromic (EC) materials on the market, such as car rearview mirrors for reducing glare, smart windows that adjust the reflection or absorption of sunlight according to changes in light, etc.

[0003] In general electrochromic hybrid materials, there are n-type materials and p-type materials. Viologen is a common n-type (i.e., cationic, color changes when it gains electrons) electrochromic material, which forms a complementary writing-erasing system with p-type (i.e., anionic, color changes when it loses electrons) electrochromic material in solution. Under the action of the electric field, the two complementary ions in the system can freely diffuse or migrate to the surface of the electrolyte. Viologen obtains electrons from the electrode and changes from an oxidized state to a reduced state. The corresponding anionic material loses electrons on the electrode and changes from a reduced state to an oxidized state. The material changes from colorless to colored. In the self-erasing process, the two ions migrate from the surface of the electrolyte to the interior of the solution. After meeting, electrons are transferred and the material fades. Common p-type materials include phenazine and phenothiazine derivatives.

[0004] As an electrochromic material, poly(3,4-propylenedioxythiophene) has the advantages of large optical contrast and fast response speed, and has great potential for industrial application. However, whether it can be applied in practice depends on the stability of the electrochromic device. The three components that play an important role in affecting its stability are the electrochromic layer, the electrolyte layer and the ion storage layer. Regarding the mechanism of the attenuation of the optical properties of electrochromism, some studies believe that in the redox cycle, the incomplete doping and dedoping of ions leads to the coverage of active sites, causing the attenuation of electrochromism. Therefore, it is proposed that the selection of doped ions that are compatible with electrochromic materials can effectively improve the stability of electrochromism. Electrochromic devices also involve the migration and transport of ions during operation. The charge balance between the ion storage layer and the electrochromic layer is crucial. Poly(3,4-propylenedioxypyrrole) (MCCP) is selected as the counter electrode material of PProDOT to form a balance of charge, which effectively improves the stability of the device. However, the most important part of the electrochromic device is the electrochromic layer, and the above adaptation may be unique. Therefore, it is very important to improve the stability of the device from the perspective of the structure of the electrochromic material itself. Therefore, how to provide a block polymer with greater solubility and no greater steric hindrance so that it can be used as an electrochromic material to prepare an electrochromic layer has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an electrochromic polymer and a preparation method and application thereof. In the present invention, by designing the structure of the electrochromic polymer, the prepared electrochromic polymer has a large solubility and does not produce a large steric hindrance, thereby not hindering the entry of doped particles, and is suitable for use as an electrochromic material to prepare an electrochromic device.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides an electrochromic polymer having a structure as shown in Formula I:

[0008]

[0009]

[0010] Wherein, R1 and R2 are each independently selected from any one of a hydrogen atom, a C2-C20 acyl group, and a C1-C20 straight chain or branched chain alkyl group, and R3 is a C1-C18 straight chain or branched chain alkyl group;

[0011] a and c are integers greater than 0, and b is an integer ≥ 0;

[0012] n is an integer from 3 to 100.

[0013] In the present invention, the structure of the electrochromic polymer is designed so that the electrochromic polymer has greater planarity, can form dense molecular stacking, and the two N atoms on the quinoxaline group have strong electron-withdrawing ability. By introducing a single alkoxy group on the quinoxaline group, the solubility of the electrochromic polymer can be effectively improved, and the prepared electrochromic polymer will not produce a large steric hindrance, thereby not hindering the entry of doped particles. The electrochromic polymer provided by the present invention is suitable for use as an electrochromic material to prepare an electrochromic device.

[0014] In the present invention, the C2-C20 may be C2, C4, C6, C8, C10, C12, C14, C16, C18 or C20, etc.

[0015] The C1-C20 can be C1, C2, C4, C6, C8, C10, C12, C14, C16, C18 or C20, etc.

[0016] The C1-C18 may be C1, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.

[0017] n can be 3, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, etc.

[0018] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0019] As a preferred technical solution of the present invention, R1 and R2 are each independently selected from any one of butyryl, hexanoyl, octanoyl, 2-ethylhexanoyl, propyl, butyl, pentyl, hexyl, octyl or dodecyl.

[0020] Preferably, R3 is selected from any one of methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, dodecyl or tridecyl.

[0021] As a preferred technical solution of the present invention, the raw materials for preparing the electrochromic polymer include compound a and compound c;

[0022] The structural formula of the compound a is The structural formula of compound c is

[0023] The R1 and R3 have the same protection scope as above.

[0024] Preferably, the molar ratio of compound a to compound c is (1-50):1, for example, 1:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1 or 50:1, etc.

[0025] As a preferred technical solution of the present invention, the raw materials for preparing the electrochromic polymer further include compound b;

[0026] The structural formula of the compound b is

[0027] The R2 has the same protection scope as above.

[0028] Preferably, the molar ratio of compound b to compound c is (0.2-10):1, for example, it can be 0.2:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1, etc.

[0029] Preferably, the molar ratio of compound a, compound b and compound c is (1-10):(0.2-5):1, for example, it can be 2:1:2, 3:1:2, 2:1:1, 4:1:1, 6:1:1, 8:1:1, 10:1:1, 2:2:1, 2:3:1, 2:4:1, 2:5:1, 4:3:1, 7:4:1 or 8:3:1, etc.

[0030] As a preferred technical solution of the present invention, the preparation method of the compound C is prepared by the following method, which comprises the following steps:

[0031] (1) Compounds The reaction yields the compound

[0032] (2) Compounds Reaction with glyoxylic acid to obtain compound

[0033] (3) Compounds The compound c is obtained by reacting with an alcohol compound.

[0034] In the present invention, by designing the synthesis route of compound c, the structure of the electrochromic polymer is designed, so that the electrochromic polymer has greater planarity, can form dense molecular stacking, and the two N atoms on the quinoxaline group have strong electron-withdrawing ability. By introducing a single alkoxy group on the quinoxaline group, the solubility of the electrochromic polymer can be effectively improved, and the prepared electrochromic polymer will not produce a large steric hindrance, thereby not hindering the entry of doped particles. The electrochromic polymer provided by the present invention is suitable for being used as an electrochromic material to prepare an electrochromic device.

[0035] In the present invention, the reaction in step (1) is carried out in the presence of a protective gas atmosphere and a metal catalyst, wherein the protective gas comprises nitrogen and argon, and the metal catalyst comprises zinc powder;

[0036] Preferably, the reaction in step (1) is carried out in the presence of a solvent;

[0037] The solvent is an organic solvent or a mixed solvent of an organic solvent; the organic solvent is selected from acetic acid, ethanol 、 Any one of propanol and 2-methoxyethanol or a combination of at least two thereof.

[0038] Preferably, the reaction temperature in step (1) is 70-90°C, for example, it can be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C.

[0039] Preferably, the reaction in step (1) further includes a post-treatment step, and the post-treatment method includes suction filtration, water washing, liquid separation and washing.

[0040] Preferably, the reaction temperature in step (2) is 120-130°C, for example, it can be 120°C, 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C or 130°C, etc.

[0041] Preferably, the reaction time of step (2) is 2 to 4 h, for example, 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0042] Preferably, the reaction in step (2) is carried out in the presence of a solvent, and the solvent is selected from any one or a combination of at least two of ethanol, acetone, isopropanol, N,N-dimethylformamide or acetonitrile.

[0043] Preferably, the number of carbon atoms in the alcohol compound in step (3) is C1 to C18, for example, it can be C1, C2, C4, C6, C8, C10, C12, C14, C16 or C18.

[0044] Preferably, the reaction in step (3) is carried out in the presence of a catalyst, and the catalyst is selected from any one of triphenylphosphine, isooctyl alcohol or diisopropyl azodicarboxylate, or a combination of at least two thereof.

[0045] Preferably, the reaction in step (3) is carried out in the presence of a solvent, and the solvent is selected from tetrahydrofuran (THF) and / or diethyl ether;

[0046] Preferably, the reaction temperature in step (3) is 20-60°C, for example, it can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C.

[0047] Preferably, the reaction in step (3) is carried out in an inert atmosphere.

[0048] Preferably, the preparation method of compound c is prepared by the following method, which comprises the following steps:

[0049] (1) In the presence of an inert atmosphere and a metal catalyst, the compound React at 70-90°C, filter, wash with water, separate and wash to obtain the compound

[0050] (2) Compound With glyoxylic acid, react at 120-130°C for 2-4h to obtain compound

[0051] (3) In an inert atmosphere, in the presence of a catalyst, the compound The mixture is reacted with an alcohol compound at room temperature for 12 to 15 seconds to obtain the compound c.

[0052] In a second aspect, the present invention provides a method for preparing the electrochromic polymer as described in the first aspect, wherein the preparation method comprises the following steps:

[0053] The raw materials for preparing the electrochromic polymer are mixed and then subjected to polymerization reaction to obtain the electrochromic polymer.

[0054] The raw materials for preparing the electrochromic polymer include compound a and compound c, and the preparation process of the reaction is as follows:

[0055]

[0056] Wherein, R1, R3 and n have the same protection scope as above.

[0057] The raw materials for preparing the electrochromic polymer include compound a, compound b and compound c, and the preparation process of the reaction is as follows:

[0058]

[0059] Among them, R1, R2, R3, a, b, c, and n have the same protection scope as above.

[0060] As a preferred technical solution of the present invention, the temperature of the polymerization reaction is 160-180°C, for example, it can be 160°C, 162°C, 164°C, 166°C, 168°C, 170°C, 172°C, 174°C, 176°C, 178°C or 180°C.

[0061] Preferably, the polymerization reaction time is 4 to 48 h, for example, it can be 4 h, 8 h, 12 h, 16 h, 20 h, 24 h, 28 h, 32 h, 36 h, 40 h, 44 h or 48 h.

[0062] Preferably, the polymerization reaction is carried out in a protective gas atmosphere, and the protective gas includes nitrogen and argon.

[0063] Preferably, the polymerization reaction is carried out in the presence of an organic solvent.

[0064] It should be noted that the present invention has no special restrictions on the selection of organic solvents, and any organic solvent commonly used in the art is applicable, including but not limited to N,N-dimethylacetamide (DMAc).

[0065] Preferably, the polymerization reaction further includes a post-treatment step, and the post-treatment method includes purification.

[0066] In a third aspect, the present invention provides an electrochromic device, the electrochromic device comprising a first working electrode, an electrochromic layer, an electrolyte layer, an ion storage layer, and a second working electrode arranged in sequence;

[0067] The material of the electrochromic layer is the electrochromic polymer as described in the first aspect.

[0068] Preferably, the material of the electrolyte layer includes polycarbonate (PC), poly(ethylene glycol) diacrylate (PEGDA), 0.2M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and dimethoxy 2-phenylacetophenone (BDK).

[0069] Preferably, the ion storage layer is poly(3,4-ethylenedioxythiophene)·poly(styrenesulfonate) (PEDOT·PSS) prepared by screen printing.

[0070] Preferably, the first working electrode and the second working electrode may be ITO glass.

[0071] In a fourth aspect, the present invention provides an application of the electrochromic polymer as described in the first aspect in the preparation of smart windows, military camouflage products, dimming and color adjustment products, and packaging display products.

[0072] Preferably, the process for preparing smart windows, military camouflage products, dimming and color adjustment products, and packaging and display products includes a coating or printing process.

[0073] Compared with the prior art, the present invention has the following beneficial effects:

[0074] (1) In the present invention, by designing the electrochromic polymer structure and further introducing a single alkoxy group on the quinoxaline group, the solubility of the electrochromic polymer can be effectively improved, and the prepared electrochromic polymer will not produce a large steric hindrance, thereby not hindering the entry of doped particles. The electrochromic polymer provided by the present invention is suitable for use as an electrochromic material to prepare an electrochromic device.

[0075] (2) The electrochromic device prepared by the electrochromic polymer provided by the present invention has excellent performance, and its optical contrast is as high as 5.1% to 18.1%. After 100,000 cycles, the contrast decay rate is as low as 5.9 to 17%, the fading time is as short as 0.9 to 1.8 seconds, the coloring time is as short as 1.8 to 2.6 seconds, and the coloring efficiency is as high as 123.4 to 441.7 cm 2 / C. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of compound c1 provided in Synthesis Example 1 of the present invention;

[0077] Figure 2 is a schematic structural diagram of an electrochromic device provided in Application Example 1 of the present invention;

[0078] Figure 3-5 The cyclic voltammetric characteristic curves of the electrochromic devices provided in Application Examples 1-3 are respectively;

[0079] Figure 6-8 The test result diagrams are respectively for testing the optical modulation rate and the color change response speed of the electrochromic device in the coloring state and the fading state provided in the corresponding examples 1-3;

[0080] Figure 9-11 The test result diagrams are respectively for testing the stability of the electrochromic devices provided in the corresponding use cases 1-3;

[0081] Among them, 1 is the first working electrode, 2 is the electrochromic layer, 3 is the electrolyte layer, 4 is the ion storage layer, and 5 is the second working electrode. DETAILED DESCRIPTION

[0082] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0083] Synthesis example 1

[0084] This synthesis example provides a compound c1 and a preparation method thereof, and the preparation method is as follows:

[0085]

[0086] (1) Compound (100 g, 1 equivalent), zinc powder (222.6 g, 10 equivalents), acetic acid (600 ml), and pure water (600 ml) were added to a 2-liter three-necked flask, mechanically stirred and mixed, replaced with nitrogen three times, slowly heated to 80°C, stirred for reaction, and plated to determine that the reaction was over, then stopped heating and the reaction was completed;

[0087] Then the three-necked flask was moved to room temperature water and cooled to room temperature, and the reaction solution was slowly poured into ice water with continuous stirring; suction filtration was performed to obtain a white solid, which was left overnight; then the solid was washed with water three times, suction filtration was performed, and the solid was added to 1 liter of ethyl acetate to dissolve, and the orange-red organic phase was suction filtration. The pH was adjusted to 8 with a saturated sodium bicarbonate solution, and the liquid was separated. The organic phase was washed twice with pure water (1 liter), and once with saturated brine, and the organic phase was rotary evaporated and concentrated to obtain 72.4 g of a yellow solid (compound ), the yield is 47%;

[0088] (2) In a 2L four-necked flask, add compound (60 g, 0.206 mol), glyoxylic acid (50% by mass in aqueous solution) (29.4 g, 0.206 mol), ethanol (1.5 L), heated to 125 ° C and refluxed, reacted for 2 hours, cooled to room temperature, terminated the reaction, and then filtered to obtain a yellow solid, which was placed in a vacuum oven at 50 ° C and dried for 5 hours to obtain compound 51 g, yield 76.89%;

[0089] (3) Add the compound into a 1L three-necked flask. (29.6 g, 0.092 mol), triphenylphosphine (24 g, 0.092 mol), isooctyl alcohol (11.96 g, 0.092 mol), diisopropyl azodicarboxylate (18.6 g, 0.092 mol), THF (700 ml), replaced with nitrogen three times, stirred at room temperature overnight, and the reaction was detected by TLC spot plate. After the reaction was completed, the reaction solution was poured into ice water, and dichloromethane was added to extract the liquid, the organic phase was washed three times with saturated brine, dried with anhydrous sodium sulfate, and spin-dried to obtain 83 g of crude product, pure petroleum ether was used as eluent, and column chromatography obtained 17.7 g of compound c1, with a yield of 46.36%.

[0090] The compound c1 provided in Synthesis Example 1 was tested by hydrogen nuclear magnetic resonance spectrum: 1 H NMR (400MHz, Chloroform-d) δ8.56 (s, 1H), 7.85 (s, 1H), 7.76 (s, 1H), 4.55 (s, 2H), 1.88 (s, 1H), 1.39 (s, 9H), 1.03–0.89 (m, 5H). Its H NMR spectrum is shown in Figure 1 shown.

[0091] Synthesis example 2

[0092] This synthesis example provides a compound c2 and a preparation method thereof. The difference from synthesis example 1 is that the isooctyl alcohol in step (3) is replaced by an equal amount of n-octanol, and the other conditions are the same as those in synthesis example 1, to obtain compound c2 with a yield of 60.36%.

[0093] Synthesis example 3

[0094] This synthesis example provides a compound c3 and a preparation method thereof. The difference from Synthesis Example 1 is that the isooctyl alcohol in step (3) is replaced by an equal amount of 2-octyldodecanol, and the other conditions are the same as those in Synthesis Example 1 to obtain compound c3 with a yield of 35.78%.

[0095] Example 1

[0096] This embodiment provides an electrochromic polymer PTQ1 and a preparation method thereof, and the preparation method is as follows:

[0097]

[0098] Compound a (0.7 g), compound c1 (0.66 g), Pd(OAc)2 (0.035 g), K2CO3 (0.65 g), PivOH (pivalic acid, 0.049 g), and DMAc (7 ml) were added to a 50 ml schlenk tube, replaced with nitrogen three times, heated to 170°C until reflux occurred, reacted overnight for 24 hours, cooled to room temperature, added a small amount of chloroform to fully dissolve the solid, and slowly poured the reaction solution into 150 ml of stirred methanol solution. Solid precipitated immediately, and the liquid tended to be clear and yellow and transparent. 3 g of ethylenediaminetetraacetic acid (EDTA) was added, and the system became a yellow turbid liquid. Stirring was stopped, filtered, and washed twice with methanol (100 ml) to obtain a purple-black solid (mixed with EDTA). The filtrate was a yellow turbid liquid. After Soxhlet extraction with methanol, acetone, n-hexane, and chloroform, the mixture was concentrated by rotary evaporation, slowly dripped into methanol for precipitation, and stirred continuously. The purple-black solid electrochromic polymer PTQ1 (1.02 g) was filtered with filter cloth, and the yield was 58%.

[0099] Example 2

[0100] This embodiment provides an electrochromic polymer PTQ2 and a preparation method thereof, and the preparation method is as follows:

[0101]

[0102] Compound a (0.67 g), compound b (0.30 g), compound c1 (0.43 g), Pd(OAc)2 (0.035 g), K2CO3 (0.65 g), PivOH (0.049 g), and DMAc (7 ml) were added to a 50 ml schlenk tube, replaced with nitrogen three times, and gradually heated to 170 degrees Celsius until reflux occurred. After reacting overnight for 24 hours, it was cooled to room temperature, a small amount of chloroform was added to fully dissolve the solid, and the reaction solution was slowly poured into 150 ml of a stirring flask. In the stirred methanol solution, solid precipitated immediately, the liquid tended to be clear and yellow and transparent, 3 g of ethylenediaminetetraacetic acid (EDTA) was added, the system turned into a yellow turbid liquid, stirring was stopped, filtered, and washed twice with methanol (100 ml) to obtain a purple-black solid (mixed with EDTA), the filtrate was a yellow turbid liquid, and extracted with methanol, acetone, n-hexane, and chloroform respectively. The chloroform solution was concentrated by rotary evaporation, slowly dripped into methanol for precipitation, and stirred continuously. The purple-black solid electrochromic polymer PTQ2 (0.81 g) was filtered through filter cloth, and the yield was 58%.

[0103] Example 3

[0104] This embodiment provides an electrochromic polymer PTQ3 and a preparation method thereof, and the preparation method is as follows:

[0105]

[0106] Compound a (0.53 g), compound b (0.36 g), compound c1 (0.25 g), Pd(OAc)2 (0.035 g), K2CO3 (0.65 g), PivOH (0.049 g), and DMAc (7 ml) were added to a 50 ml Schlenk tube, replaced with nitrogen three times, and gradually heated to 170 degrees Celsius until reflux occurred. After reacting overnight for 24 hours, it was cooled to room temperature, a small amount of chloroform was added to fully dissolve the solid, and the reaction solution was slowly poured into 150 ml of a stirring In the stirred methanol solution, solid precipitated immediately, the liquid tended to be clear and yellow and transparent, 3 g of ethylenediaminetetraacetic acid (EDTA) was added, the system turned into a yellow turbid liquid, stirring was stopped, filtered, and washed twice with methanol (100 ml) to obtain a purple-black solid (mixed with EDTA). The filtrate was a yellow turbid liquid, which was extracted with methanol, acetone, n-hexane, and chloroform, respectively. The chloroform solution was concentrated by rotary evaporation, slowly dripped into methanol for precipitation, and stirred continuously. The purple-black solid electrochromic polymer PTQ3 (0.56 g) was filtered through filter cloth, and the yield was 49%.

[0107] Example 4

[0108] This embodiment provides an electrochromic polymer PTQ4 and a preparation method thereof. The difference from Embodiment 2 is that the compound c1 is replaced by the compound c2 of the same substance amount, and the other conditions are the same as those of Embodiment 2.

[0109] Example 5

[0110] This embodiment provides an electrochromic polymer PTQ5 and a preparation method thereof. The difference from Embodiment 2 is that the compound c1 is replaced by the compound c3 of the same substance amount, and the other conditions are the same as those of Embodiment 2.

[0111] Comparative Example 1

[0112] This comparative example provides an electrochromic polymer and a preparation method thereof, which differs from Example 2 only in that compound c1 is replaced by an equal amount of compound (purchased from Suzhou Nakai Technology Co., Ltd.), wherein R is ethylhexyl, and other conditions are the same as in Example 2.

[0113] Comparative Example 2

[0114] This comparative example provides an electrochromic polymer and a preparation method thereof, which differs from Example 2 only in that compound c1 is replaced by an equal amount of compound (purchased from Suzhou Nakai Technology Co., Ltd.), wherein R is ethylhexyl, and other conditions are the same as in Example 2.

[0115] Application Example 1

[0116] This application example provides an electrochromic device, which includes a first working electrode, an electrochromic layer, an electrolyte layer, an ion storage layer, and a second working electrode, which are arranged in sequence.

[0117] The first working electrode and the second working electrode are ITO glass;

[0118] The material of the electrochromic layer is electrochromic polymer PTQ1;

[0119] The materials of the electrolyte layer are a gel polymer electrolyte of polycarbonate (PC), poly(ethylene glycol) diacrylate (PEGDA), 0.2 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and dimethoxy 2-phenylacetophenone (BDK);

[0120] The material of the ion storage layer is poly(3,4-ethylenedioxythiophene)·poly(styrene sulfonate) (PEDOT·PSS).

[0121] The preparation method of the electrochromic device is as follows:

[0122] (1) cleaning two pieces of ITO glass and treating them with O-plasma to obtain a first working electrode and a second working electrode;

[0123] (2) The electrochromic polymer PTQ1 was dissolved in xylene to obtain a mixed solution (80 mg / mL), and then the mixed solution was mechanically filtered to remove impurities, and then statically spin-coated (spin-coated at 600 rpm for 6 seconds and then spin-coated at 4000 rpm for 30 seconds) to one side of the first working electrode to obtain an electrochromic layer with an effective area of ​​2.5×3.0 cm;

[0124] (3) coating a gel polymer electrolyte composed of polycarbonate (PC), poly(ethylene glycol) diacrylate (PEGDA), 0.2 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and dimethoxy 2-phenylacetophenone (BDK) on a side of the electrochromic layer away from the first working electrode to obtain an electrolyte layer;

[0125] (4) screen printing poly(3,4-ethylenedioxythiophene)·poly(styrene sulfonate) onto the side of the electrolyte layer away from the electrochromic layer to obtain an ion storage layer;

[0126] (5) The second working electrode is placed on the side of the ion storage layer away from the electrolyte layer, and the edges are sealed with double-sided tape to obtain an electrochromic device.

[0127] Application Example 2-5

[0128] Application Examples 2-5 respectively provide an electrochromic device, which differs from Application Example 1 only in that the electrochromic polymer PTQ1 of the electrochromic layer is replaced with electrochromic polymers PTQ2-PTQ5 in sequence, and other conditions are the same as those of Application Example 1.

[0129] Using Chenhua electrochemical workstation CHI660E, the cyclic voltammetric characteristic curves of the electrochromic device provided in Example 1-3 were tested respectively. The cyclic voltammetric characteristic curves are as follows: Figure 3-5 As shown. Figure 3-5 It can be seen that the electrochromic polymers 1-3 provided by the present invention all have good electrochemical cycle performance and a certain charge storage capacity.

[0130] Using Chenhua electrochemical workstation CHI660E and Lambda 750 spectrophotometer, the optical modulation rate and color change response speed of the electrochromic device in the coloring state and fading state provided in Example 1-3 were tested. The test results are shown in Figure 6-8 As shown. Figure 6-8 It can be seen that the electrochromic device prepared with the electrochromic polymer provided by the present invention has a good optical modulation rate and a fast color change response speed. Among them, the electrochromic device provided in Application Example 3 achieves a fading time of 0.9 seconds and a coloring time of 1.8 seconds.

[0131] The stability of the electrochromic device provided in Example 1-3 was tested using a Lambda 750 spectrophotometer. The test results are shown in Figure 9-11 As shown. Figure 9-11 It can be seen that the electrochromic device prepared by the electrochromic polymer provided by the present invention has good cycle stability.

[0132] Application Comparative Example 1-2

[0133] Application Comparative Examples 1-2 respectively provide an electrochromic device, which differs from Application Example 1 only in that the electrochromic polymer 1 of the electrochromic layer is replaced with the electrochromic polymers provided by Application Comparative Examples 1-2 in sequence, and other conditions are the same as those of Application Example 1.

[0134] The performance of the electrochromic device provided in Example 1-5 and Comparative Example 1-2 was tested, and the test method was as follows:

[0135] (1) Starting voltage: Test instrument: electrochemical workstation, test method: cyclic voltammetry; test conditions: 50 mV / s, voltage range: 2000 mV to -2000 mV, number of cycles: 8, current setting range: 2.5 × 10 -3 mA, starting voltage value: make the intersection of the tangent line of the curve and y=0.

[0136] (2) Maximum absorption wavelength: Test instrument: Lambda750, Test method: Absorption spectrum, Test conditions: Spectral range: 400-800nm, Sampling interval: 1nm, Maximum absorption wavelength value: Test the transmittance spectra of the above-mentioned device in the colored state and the transmitted state respectively, and take the wavelength with the largest transmittance difference as the maximum absorption wavelength.

[0137] (3) Optical contrast: Test instrument: electrochemical workstation combined with Lambda750, Test instrument: electrochemical workstation combined with Lambda750, Test method: transmittance time spectrum, Test conditions: electrochemical workstation: forward voltage: fading voltage, time: 10s, reverse voltage: coloring voltage, time: 10s, Lambda750: wavelength: maximum absorption wavelength, time: 12 minutes, sampling interval: 0.2s, Test method: transmittance (T%), Value: transmittance in fading state - transmittance in colored state.

[0138] (4) Contrast decay rate: Test instrument: function generator + electrochemical workstation in conjunction with Lambda750. Test method: perform step cycles on the function generator and then test the optical contrast. The value is: (optical contrast before the cycle - optical contrast after the cycle) / optical contrast before the cycle.

[0139] (5) Fading time: Test instrument: electrochemical workstation combined with Lambda750, test method: transmittance time spectrum, test conditions: electrochemical workstation: forward voltage: fading voltage, time: 10s, reverse voltage: coloring voltage, time: 10s, Lambda750: wavelength: maximum absorption wavelength, time: 12 minutes, sampling interval: 0.2s, test method: transmittance (T%), value: the time required for the transmittance change from the fading state to the coloring state to reach 95% of the optical contrast.

[0140] (6) Coloring time: Test instrument: electrochemical workstation combined with Lambda750, test method: transmittance time spectrum, test conditions: electrochemical workstation: forward voltage: fading voltage, time: 10s, reverse voltage: coloring voltage, time: 10s, Lambda750: wavelength: maximum absorption wavelength, time: 12 minutes, sampling interval: 0.2s, test method: transmittance (T%), value: the time required for the transmittance change from the colored state to the faded state to reach 95% of the optical contrast.

[0141] (7) Coloring efficiency: Test instrument: Electrochemical workstation combined with Lambda750, Test method: Transmittance time spectrum, Test conditions: Electrochemical workstation: Forward voltage: Fading voltage, Time: 10 s, Reverse voltage: Coloring voltage, Time: 10 s, Lambda750: Wavelength: Maximum absorption wavelength, Time: 12 minutes, Sampling interval: 0.2 s, Test method: Transmittance (T%), Value: Q / A is the x-axis, with (log(T / T c )) is the y-axis, and the slope of the tangent is taken as the coloring efficiency. Q: current passing through per unit time, A: effective area of ​​the device, T: transmittance, T c : Transmittance in the colored state, T b : Transmittance in faded state.

[0142] The performance test results of the electrochromic devices provided by Application Examples 1-5 and Comparative Application Examples 1s-2s are shown in Table 1 below:

[0143] Table 1

[0144]

[0145]

[0146] As can be seen from the contents of Table 1, the present invention can effectively improve the solubility of the electrochromic polymer by designing the electrochromic polymer structure and further introducing a single alkoxy group on the quinoxaline group, and the prepared electrochromic polymer will not produce a large steric hindrance, thereby not hindering the entry of doped particles. The electrochromic device prepared in this way has excellent performance, with a high optical contrast of 5.1% to 18.1%, a low contrast attenuation rate of 5.9 to 17% after 100,000 cycles, a short fading time of 0.9 to 1.8 s, a short coloring time of 1.8 to 2.6 s, and a high coloring efficiency of 123.4 to 441.7 cm 2 / C.

[0147] In the present invention, three compounds (compound a, compound b and compound c) are further used as raw materials for preparing the electrochromic polymer, so that the comprehensive performance of the electrochromic polymer can be further improved. The electrochromic device prepared by the electrochromic polymer has a starting voltage of -0.25 to 0.17 V, a high optical contrast of 14.8% to 18.1%, a low contrast attenuation rate of 5.9 to 9.6% after 100,000 cycles, a short fading time of 0.9 to 1.1 s, a short coloring time of 1.8 to 2.6 s, and a high coloring efficiency of 389.6 to 441.7 cm 2 / C.

[0148] Compared with Application Example 2, if the material used to prepare the electrochromic layer has two alkoxy groups on the quinoxaline group in the electrochromic polymer (Comparative Application Example 1) or two alkyl groups on the quinoxaline group in the electrochromic polymer (Comparative Application Example 2), the overall performance of the prepared electrochromic device is poor.

[0149] In summary, the present invention designs the electrochromic polymer structure and further introduces a single alkoxy group on the quinoxaline group, so that the solubility of the electrochromic polymer can be effectively improved, and the prepared electrochromic polymer will not produce a large steric hindrance, thereby not hindering the entry of doped particles. The electrochromic device prepared in this way has excellent performance.

[0150] The applicant declares that the present invention illustrates the detailed structural features and detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features and detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features and detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, the equivalent replacement of the components selected by the present invention, the addition of auxiliary components, the selection of specific methods, etc., the equivalent replacement of the raw materials of the product of the present invention, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An electrochromic polymer, characterized in that The electrochromic polymer has a structure as shown in Formula I: Wherein, R1 and R2 are each independently selected from any one of a hydrogen atom, a C1-C20 acyl group, and a C1-C20 straight-chain or branched-chain alkyl group, and R3 is a C1-C18 straight-chain or branched-chain alkyl group; a and c are integers greater than 0, and b is an integer ≥ 0; n is an integer from 3 to 100.

2. The electrochromic polymer according to claim 1, characterized in that The R1 and R2 are each independently selected from any one of butyryl, hexanoyl, octanoyl, 2-ethylhexanoyl, propyl, butyl, pentyl, hexyl, octyl or dodecyl.

3. The electrochromic polymer according to claim 1, characterized in that The R3 is selected from any one of methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, dodecyl or tridecyl.

4. The electrochromic polymer according to claim 1, characterized in that The raw materials for preparing the electrochromic polymer include compound a and compound c; The structural formula of the compound a is The structural formula of compound c is The R1 and R3 have the same protection scope as that of claim 1.

5. The electrochromic polymer according to claim 4, characterized in that The molar ratio of compound a to compound c is (1-50):

1.

6. The electrochromic polymer according to claim 4, characterized in that The raw materials for preparing the electrochromic polymer also include compound b; The structural formula of the compound b is The R2 has the same protection scope as that of claim 1.

7. The electrochromic polymer according to claim 6, characterized in that The molar ratio of compound b to compound c is (0.2-10):

1.

8. The electrochromic polymer according to claim 6, characterized in that The molar ratio of compound a, compound b and compound c is (1-10):(0.2-5):

1.

9. The electrochromic polymer according to claim 4, characterized in that The preparation method of the compound C is prepared by the following method, which comprises the following steps: (1) Compounds The reaction yields the compound (2) Compounds Reaction with glyoxylic acid to obtain compound (3) Compounds The compound c is obtained by reacting with an alcohol compound.

10. The electrochromic polymer according to claim 9, characterized in that The reaction temperature in step (2) is 120-130°C.

11. The electrochromic polymer according to claim 9, characterized in that The reaction time of step (2) is 2 to 4 hours.

12. The electrochromic polymer according to claim 9, characterized in that The number of carbon atoms in the alcohol compound in step (3) is C1 to C18.

13. The electrochromic polymer according to claim 9, characterized in that The reaction in step (3) is carried out in the presence of a catalyst, wherein the catalyst is selected from any one of triphenylphosphine, isooctyl alcohol or diisopropyl azodicarboxylate or a combination of at least two thereof.

14. The electrochromic polymer according to claim 9, characterized in that The reaction temperature in step (3) is 20-60°C.

15. A method for preparing an electrochromic polymer according to any one of claims 1 to 14, characterized in that: The preparation method comprises the following steps: The raw materials for preparing the electrochromic polymer are mixed and then subjected to polymerization reaction to obtain the electrochromic polymer.

16. The preparation method according to claim 15, characterized in that: The polymerization reaction temperature is 160-180°C.

17. The preparation method according to claim 15, characterized in that: The polymerization reaction time is 4 to 48 hours.

18. An electrochromic device, characterized in that: The electrochromic device comprises a first working electrode, an electrochromic layer, an electrolyte layer, an ion storage layer, and a second working electrode arranged in sequence; The material of the electrochromic layer is the electrochromic polymer according to any one of claims 1 to 14.

19. Use of the electrochromic polymer according to any one of claims 1 to 14 in the preparation of smart windows, military camouflage products, dimming and color adjustment products, and packaging display products.

20. The use according to claim 19, characterized in that The process for preparing smart windows, military camouflage products, dimming and color adjustment products, and packaging and display products includes coating or printing processes.

Citation Information

Patent Citations

  • Green polythiophenes electrochromic material and preparation method thereof as well as component

    CN103772664A

  • Quinoxaline-based conjugated polymer, and preparation method and application thereof in polymer solar batteries

    CN108948327A